Peranan Kelompok Tani Sehat terhadap Keberhasilan Penyaluran Pupuk Bersubsidi di Nagori Dolok Marlawan Kabupaten Simalungun Provinsi Sumatera Utara - SINTIKHE AMELIA SIMANJUNTAK; I KETUT SURYA DIARTA; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Role Of “Sehat” Farming Group on Distributing Subsidized Fertilizer Successfully In Nagori Dolok Marlawan, Simalungun District, North Sumatera Farming group has important role on rural development strategy. For supporting inclination of agriculture products, farming group act as distribution of subsidized fertilizer to farmers so that famers can manage their land properly. The role also can be done by Farming Group “Sehat” in Nagori Dolok Marlawan, Simalungun District, North Sumatera. The mechanism of subsidized fertilizer could be done the official government help farming group board on calculating the need of fertilizer for farming group members. The data should be collected directly from farmers and the results of calculation must be created as Rencana Definitif Kebutuhan Kelompok (RDKK) or definitive plan for group need. The research explore the role of Farming Group “Sehat” on distributing subsidized fertilizer fairly to all of its member. Data on this research was generated by interviewing key informants and distributing questionnaire to the farmers. The data had been analyzed with statistical methods and presented with qualitative description. The research figure out that three variable of farming group role such as farming group preparing RDKK data, farming groups provide RDKK data to distributors and farming groups when distributing fertilizer that have supported a good system on distributing subsidized fertilizer. However a variable that is internal and external factors of farmers was defined as obstacle ondistributing subsidized fertilizer. Because of those findings, it can be conclude that Farming Group “Sehat” can create good RDKK and distribute subsidized fertilizer effectively.